Pelatihan Microsoft Word Bagi Santri di Dayah Darul Huda Alue Udep - Jamali; Erniwiriani (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
This Microsoft Word training was conducted at Dayah Darul Huda Alue Udep with the goal of enhancing the digital skills of the santri in using word processing software essential for academic and administrative tasks. The training employed a combination of theoretical and practical approaches, equipping participants with both basic and advanced skills in using Microsoft Word, such as document creation, formatting, table creation, and the preparation of reports and official letters. The results of the training showed significant improvement in the santri’s ability to use Microsoft Word, as evidenced by their increased efficiency in completing academic and administrative tasks. Additionally, the training fostered independent learning habits through the use of digital learning media, allowing participants to continue their learning beyond the training sessions. This training is expected to have a positive impact on increasing the productivity of the santri and preparing them to face the challenges of the increasingly digital world.